Hybrid Photodynamic Therapy as a Component of Combined Treatment of Uveal Melanoma (Preliminary Results) - E. V. Boiko; E. V. Samkovich; I. E. Panova; E. M. Svistunova; A. A. Ivanov; A. A. Bikhovsky (Oftalʹmologiâ, 2024)
Objective. To develop a technique of hybrid photodynamic therapy (PDT) and present its preliminary results in combined organ-preserving treatment of uveal melanoma (UM).Materials and methods. 4 patients with UM (T2aN0M0 — 2 patients, T3aN0M0 — 2 patients) were treated by hybrid PDT followed by Ru-106 + Rh-106 brachytherapy (BT). The initial UM prominence ranged from 7 to 8.6 mm (7.92 ± 0.67 mm), and the tumor base diameter ranged from 10.3 to 14 mm (12.10 ± 1.89 mm). PDT was performed using a chlorine photosensitizer at a rate of 1.0 mg/kg weight using a new hybrid technology, which consists of transpupillary and transscleral exposure to the tumor in one treatment session. Ru-106 + Rh-106 BT was performed according to the standard technique for up to 1 month after PDT.Results. The combined approach contributed to rapid rates of tumor regression at the early terms of dynamic follow-up and achievement of complete regression at the period of 12 months in 2 cases with initially “large” UM sizes. Decrease in the signs of intratumoral vascularization of UM was noted from the first month of follow-up and this tendency was maintained throughout the whole period.Conclusions. The presented preliminary results of hybrid PDT in combined treatment of UM expand the possibilities of organ-preserving treatment of largesized tumors due to direct cytotoxic and antiangiogenic effects on tumor substrate, as well as potentiation of radiation therapy.